PENGEMBANGAN MEDIA 3D PAGEFLIP E- BOOK UNTUK HASIL BELAJAR PADA MATA PELAJARAN IPA KELAS V SDN 22 SUNGAI AMBAWANG - Siti Musripah; Aloysius Mering; Fadillah Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
Abstract       The main problem that is problem in understanding of IPA caused by some matter in science lesson include abstract stuff, which can not be analyzed directly with the sense of sight so that is difficult to be understood by learners, therefore need media learning media media pageflip e-book In order to help learners in improving the learning process and learning outcomes especially on science subjects for circulatory organ material. 3D media pageflip e-book in science lessons This study uses the development stage of Borg and Gall, with the subject of research is the V-class students of 19 people. Data were obtained through expert validation questionnaires, observations, interviews, student response questionnaires, and documentation. Further data analysis is done on the results of expert validation, observation, interview and questionnaire response of learners. it can be seen from the pretest result that is before the learning process using 3D media pageflip e-book 94% not complete and 6 % Completion that has increased in poststroke result that is after learning process using 3D media pageflip e-book is 100% complete and 0% unfinished, so from that percentage of students progress in learning process of circulation organs using 3D media pagefli e -book.  Key words: 3D Media pageflip E-Book, Organ Circulation, Borg and Gall.